2024
DOI: 10.3390/fermentation10010043
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid Bacteria and Formic Acid Improve Fermentation Quality and Beneficial Predicted Functional Characteristics in Mixed Silage Consisting of Alfalfa and Perennial Ryegrass

Yao Lei,
Maoya Li,
Yinghao Liu
et al.

Abstract: The purpose of the present study was to investigate the effect of additives on the fermentation properties of ensiled mixed alfalfa and perennial ryegrass silage in the karst terrain of Southwest China. A mixture of alfalfa and perennial ryegrass was ensiled at a ratio of 3:7 using three experimental treatments: (1) CK (without additives) and distilled water (5 mL kg−1 fresh weight (FW)); (2) FA and formic acid (88%) (5 mL kg−1 FW); and (3) LAB combined with the application of Lactiplantibacillus plantarum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…Chemical additives reduced NH 3 -N content in WPS silage indicating lower proteolysis during silage fermentation, which is further confirmed by the greater concentration of CP observed in these silages when compared to other treatments. Aligning with the current study, authors have reported that chemical additives with organic acids are able to decrease ammonia N content in mixed legume-grass silage [28]. It is important to note that fermentation parameters and metabolites were assessed at the opening of the silos, and they cannot represent the fermentation dynamics throughout the silage storage period.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Chemical additives reduced NH 3 -N content in WPS silage indicating lower proteolysis during silage fermentation, which is further confirmed by the greater concentration of CP observed in these silages when compared to other treatments. Aligning with the current study, authors have reported that chemical additives with organic acids are able to decrease ammonia N content in mixed legume-grass silage [28]. It is important to note that fermentation parameters and metabolites were assessed at the opening of the silos, and they cannot represent the fermentation dynamics throughout the silage storage period.…”
Section: Discussionsupporting
confidence: 71%
“…In whole-plant corn silage, WSC concentration and pH at opening were similar between silage treated with LAB and with organic acids [27]. In a mixed silage (alfalfa and perennial ryegrass), the pH was lower and WSC was greater in silages treated with formic acid regardless of the storage period (7, 15, or 45 d) in comparison with those treated with LAB [28]. Regarding comparisons between chemical additives, silages treated with FA type had greater concentrations of NFC than those silages treated with PA type, aligning with lower silage pH at opening for FA silos in comparison with PA type.…”
Section: Discussionmentioning
confidence: 86%